The effect of immersion times on the solubility and bonding stress of hydroxyapatite coated Ti6al4v pedicle screws - Aksakal, Bunyamin (Wichtig Editore, 2010)
Purpose: Main aim of the present study was to test and show the dissolution of coatings onto Ti6Al4V pedicle screws by both in vitro and in vivo analysis. Methods: Hydroxyapatite (HA) was coated on Ti6Al4V by electrophoretic deposition (EPD). The dissolution of the coatings was tested in vitro. The coating was characterized before and after implantation via pull-out tests, X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The coating materials were immersed in a simulated body fluid (SBF) from 1 day to 6 weeks, in vitro, and the elemental analysis were undertaken in a calf spine, in vivo. Fourteen coated (7) and uncoated (7) Ti6Al4V pedicle screws were implanted in a calf spine for 12 weeks and the elemental concentration was analyzed using the wavelength dispersive X-ray fluorescence (WDXRF) technique. Results: The analysis of elemental concentrations by WDXRF are presented and 97% of the dissolved elements were determined as Ca, P, Ti, O and 3% of K, Na, Fe, Ni, Zn, Mg, S in total. The solubility of the coating materials increased with increasing immersion time and, interestingly, it increased substantially for reasonably longer times, for example, 6 weeks. Conclusions: Through the in vivo experiments, on the HA coated and uncoated pedicle screws implanted on a calf vertebra, the elemental concentrations by WDXRF analysis showed the Ca(%) around the pedicle screws increased by 30% after re-implantation process. The results may lead us to reconsider such ceramic coatings to test in vitro and/or in vivo for longer periods before clinical applications. (Journal of Applied Biomaterials & Biomechanics 2010; 8: 33-41)
Keywords: Biomedical materials; Pedicle screws; Coatings; Hydroxyapatite; Dissolution